Analisis Organizational Trust dan Komitmen Organisasi terhadap Turnover Intention pada Pekerja Generasi Milenial dengan Kepuasan Kerja sebagai Variabel Intervening - Putri Nugraheni Cahyaningsih; Kusuma Chandra Kirana; Henny Welsa (J-MAS (Jurnal Manajemen dan Sains), 2021)
This study aims to examine and analyze the analysis of organizational trust, organizational commitment, job satisfaction and turnover intention in millennial generation workers in the Special Region of Yogyakarta. The main problem is turnover intention. Data was collected by distributing questionnaires via google forms to 292 respondents spread across the Special Region of Yogyakarta. The method used in this study uses quantitative research methods using purposive random sampling data collection techniques and using Partial Least Square (PLS) for analysis tools. Based on the results of the analysis, it is found that the factors that influence turnover intention are organizational trust and job satisfaction. This is evidenced by the results of hypothesis testing which show P Values <0.05, which is 0.000 and P Value <0.05, which is 0.025, while the organizational commitment variable has no effect on turnover intention in millennial generation workers in the Special Region of Yogyakarta.